Structural and biochemical mechanisms of NLRP1 inhibition by DPP9 - Huang, Menghang (2022)
Nucleotide-binding domain, leucine-rich repeat receptors (NLRs) mediate innate immunity by forming inflammasomes. Activation of the NLR protein NLRP1 requires autocleavage within its function-to-find domain (FIIND)1-7. In resting cells, the dipeptidyl peptidases DPP8 and DPP9 interact with the FIIND of NLRP1 and suppress spontaneous NLRP1 activation8,9; however, the mechanisms through which this occurs remain unknown. Here we present structural and biochemical evidence that full-length rat NLRP1 (rNLRP1) and rat DPP9 (rDPP9) form a 2:1 complex that contains an autoinhibited rNLRP1 molecule and an active UPA-CARD fragment of rNLRP1. The ZU5 domain is required not only for autoinhibition of rNLRP1 but also for assembly of the 2:1 complex. Formation of the complex prevents UPA-mediated higher-order oligomerization of UPA-CARD fragments and strengthens ZU5-mediated NLRP1 autoinhibition. Structure-guided biochemical and functional assays show that both NLRP1 binding and enzymatic activity are required for DPP9 to suppress NLRP1 in human cells. Together, our data reveal the mechanism of DPP9-mediated inhibition of NLRP1 and shed light on the activation of the NLRP1 inflammasome.